Additions to the genus Chroogomphus (Boletales, Gomphidiaceae) from Pakistan - Kiran, Munazza; Sattar, Ammara; Zamir, Khushbakht; Haelewaters, Danny; Khalid, Abdul Nasir (MycoKeys, 2020)
With only three published reports, the genus Chroogomphus (Boletales, Gomphidiaceae) is poorly studied in Pakistan. During recent sampling events in Khyber Pakhtunkhawa province, Pakistan, several collections of Chroogomphus were made, representing undescribed taxa. Based on morphological and molecular data, two new species are described: Chroogomphus pakistanicus and C. pruinosus. We present a description and illustrations for both taxa. A molecular phylogenetic reconstruction, based on the internal transcribed spacer (ITS1-5.8S-ITS2) barcode region, shows that C. pakistanicus and C. pruinosus are placed in two different subgenera of Chroogomphus (subg. Chroogomphus and subg. Siccigomphus, respectively).
Keywords: Basidiomycota; Boletales; coniferous forests; macrofungi; taxonomy; phylogeny; 2 new taxa